Chest tube drainage versus needle aspiration for primary spontaneous pneumothorax: which is better? - Wang, Chengdi (J Thorac Dis, 2017)
BACKGROUND: Needle aspiration and chest tube drainages are two main treatments for primary spontaneous pneumothorax (PSP). However, the application of needle aspiration or chest tube drainages has not reached a consensus. The aim of this study is to compare the needle aspiration with chest tube drainages in patients suffering with PSP and therefore help offer suggestions for clinical practice. METHODS: We searched literatures from PubMed, OVID and Web of Science from their inception to June 30, 2017. Continuous and dichotomous outcomes were expressed by weight mean difference (WMD) and risk ratio (RR) respectively, and each with 95% confidence intervals (CIs). We used the fixed effect or random effect model to perform quantitative synthesis. RESULTS: A total of 6 RCTs recruiting 458 participants were included in our analysis. On the basis of the six studies, our results indicated that compared with chest tube drainage applying needle aspiration shortened the hospital stay (WMD: ‒1.67 days; 95% CI: ‒2.25 to 1.08; P<0.001) and decreased hospitalization rate (RR: 0.40; 95% CI: 0.22–0.75; P=0.004). However, there was no difference regarding immediate success rate (RR: 1.01; 95% CI: 0.70–1.46; P=0.96) and one-year recurrence rate (RR: 0.89; 95% CI: 0.58–1.38; P=0.61). CONCLUSIONS: In the light of this present research, it is necessary to apply needle aspiration into treating PSP to reduce hospitalization rate and shorten hospital stay. However, the two treatments have no significant difference with respect to immediate success rate, one-year recurrence rate, one-week success rate, three-month recurrence rate or complication rate.